Globalization: a basic text - Ritzer, George (Sussex, 2010)
The first full-scale textbook of its kind, Globalization provides a balanced introduction to the major topics in globalization studies. Develops a unique perspective on globalization early in the book and uses it throughout to orient and organize discussion of a wide range of topics and parts of the world Integrated use of a wide array of materials - empirical research, theories, newspaper and magazine articles, monographs, popular books, etc Makes extensive use of maps throughout to illustrate key points about globalization Includes a glossary of key terms Designed to work either on its own or as a package with an accompanying cross-referenced reader constructed around the basic concepts of globalization.
Keywords: Globalization